The value of a collaborative course for advanced head and neck surgery in East Africa. (21st November 2014) - Chambers, Kyle J.; Aswani, Joyce; Patel, Asmeeta; Fundakowski, Christopher; Mannion, Kyle; Lin, Derrick T.; Netterville, James
Abstract : Objectives/Hypothesis: To determine the value of a collaborative course for advanced head and neck surgery in East Africa. Study Design: Survey of participants. Methods: A 3‐day course in head and neck surgery was designed for otolaryngologists and trainees from Kenya and surrounding countries through a collaborative effort between Kenyatta National Hospital, the University of Nairobi, and the Head and Neck Divisions from the Vanderbilt Bill Wilkerson Center and the Massachusetts Eye and Ear Infirmary. Topics included neck dissection, parotidectomy, total laryngectomy, parapharyngeal space tumors excision, and pectoralis myocutaneous flaps. A pre‐ and postcourse self‐evaluation survey was administered to measure course impact. Results: Eighteen otolaryngologists and trainees participated in the course, with 17 completing course surveys. The majority of participants (72%) were from Kenya. Prior to the start of the course, 41%, 71%, 23%, 12%, and 0% of participants indicated they could complete a neck dissection, parotidectomy, parapharyngeal space mass excision, total laryngectomy, and pectoralis myocutaneous flap, respectively. Following the course, 50%, 94%, 69%, 25%, and 38% of participants indicated they could complete a neck dissection, parotidectomy, total laryngectomy, parapharyngeal space tumors excision, respectively, with a statistically significant increase identified for pectoralis myocutaneous flaps ( P  < .001) and total laryngectomy ( P  = .009). There was also a trend toward an increase in the number of participants indicating an ability to complete parotidectomy following the course ( P  = .085). Conclusions: This survey demonstrates the potential value of a collaborative course in advanced head and neck surgery as one useful model for increasing the number of well‐trained head and neck surgeons in East Africa. Level of Evidence: NA Laryngoscope, 125:883–887, 2015